Enhancing the Catalytic Activity of MOF‐808 Towards Peptide Bond Hydrolysis through Synthetic Modulations. Issue 68 (29th November 2021) - Simms, Charlotte; de Azambuja, Francisco; Parac‐Vogt, Tatjana N.
Abstract: The performance of MOFs in catalysis is largely derived from structural features, and much work has focused on introducing structural changes such as defects or ligand functionalisation to boost the reactivity of the MOF. However, the effects of different parameters chosen for the synthesis on the catalytic reactivity of the resulting MOF remains poorly understood. Here, we evaluate the role of metal precursor on the reactivity of Zr‐based MOF‐808 towards hydrolysis of the peptide bond in the glycylglycine model substrate. In addition, the effect of synthesis temperature and duration has been investigated. Surprisingly, the metal precursor was found to have a large influence on the reactivity of the MOF, surpassing the effect of particle size or number of defects. Additionally, we show that by careful selection of the Zr‐salt precursor and temperature used in MOF syntheses, equally active MOF catalysts could be obtained after a 20 minute synthesis compared to 24 h synthesis. Abstract : Modulating the synthesis of MOF‐808 through choice of zirconium precursor directly impacts its structure and reactivity towards the hydrolysis of peptide bonds, outweighing the influence of MOF defects or particle size.